Buckling of Rectangular Plates Under Discontinuous Loading Along Boundaries - J. Golec (Engineering Transactions)
The paper deals with a problem of buckling of the elastic isotropic elastically homogeneous rectangular plates of small thickness, loaded arbitrarily along the boundaries, at the different boundary conditions assumed.